2017
DOI: 10.1002/pca.2686
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Volatile Flavour Profiles of Citrus spp. Fruits by SDE‐GC–MS and Enantiomeric Composition of Chiral Compounds by MDGC–MS

Abstract: The enantiomeric composition and excess ratios of the chiral compounds could be used as reliable indicators of genuineness and quality assurance of the oils derived from the Citrus fruit species. Copyright © 2017 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 42 publications
(46 reference statements)
1
18
0
Order By: Relevance
“…Only two studies 4,19 described the proper analysis of Yuzu oil by chiral GC, and their results are reported in Table 3. It appears that all the Yuzu oil constituents mentioned in these studies are characterized by high enantiomeric purity.…”
Section: Chemical Composition Of Yuzu Peel Oilmentioning
confidence: 99%
“…Only two studies 4,19 described the proper analysis of Yuzu oil by chiral GC, and their results are reported in Table 3. It appears that all the Yuzu oil constituents mentioned in these studies are characterized by high enantiomeric purity.…”
Section: Chemical Composition Of Yuzu Peel Oilmentioning
confidence: 99%
“…Species of Citrus fruits, such as C. hystrix [22], C. australasica [23], C. junos , C. limon and C. aurantifolia [24], and the Citrus -like Eustis limequat fruit [25] were analysed by MDGC and GC×GC techniques which proved to be efficient tools to differentiate odorants, varieties and origins, as well as reliably separate, identify and quantify their chiral compounds.…”
Section: Foodmentioning
confidence: 99%
“…Delort et al [23] and Hong et al [24] assessed enantiomeric ratios of the chiral aroma volatiles from Australian finger lime ( Citrus australasica ) and other three Citrus species ( C. junos , C. limon and C. aurantifolia ), respectively, using MDGC systems. In the former work, the authors identified six new terpenyl esters and some isomers in the finger lime samples: 6-methyloctyl acetate, citronellyl citronelate, 1,2:5,6-diepoxy- p -menthane, 2,3-epoxy- p -menthan-6-one, cis- and trans - p -menth-1-en-3-ol-6-one and 1,2-epoxy- p -methan-5-one, some of them reported for the first time in a natural product.…”
Section: Foodmentioning
confidence: 99%
See 1 more Smart Citation
“…Swingle (lime). They demonstrated the utility of this technique to determine the botanical origin of fruits based on the analysis of the volatile chiral compounds, i.e., α-pinene, camphene, sabinene, limonene, and β-phellandrene [7]. The disadvantage of this solution is the time taken for a single analysis [8].…”
Section: Introductionmentioning
confidence: 99%